Kemampuan Guru Dalam Menerapkan Pembelajaran Fikih Berbasis Hots di Madrasah Muhammadiyah Mandiangin Kabupaten Banjar - hayatina, maulida (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
The basic problem in this research is the teacher's ability to teach fiqh at MTs Muhammadiyah Mandiangin, Banjar Regency. The data was obtained from the results of preliminary studies, such as the large number of passive students in class, students who are less able to think critically, and from the teacher's point of view additional knowledge is needed regarding the latest learning models, especially in implementing the 2013 curriculum. Based on these conditions, this study aims to determine the ability of teachers to apply HOTS-based fiqh learning at MTs Muhammadiyah Mandiangin. This study uses a qualitative approach. The subjects in this study were the fiqh teachers at MTs Muhammadiyah Mandiangin and the objects in this study were the nature of the state of the fiqh learning process. Data collection techniques using interviews, observation, and documentation. The data processing techniques include editing, description, and interpretation of data. Data analysis used is descriptive qualitative analysis. The results of this study indicate that MTs Muhammadiyah Mandiangin teachers have a fairly good ability to use the HOTS learning model so that the learning process is more active. Indicators of this ability can also be seen from the teacher's ability to prepare lesson plans, and the teacher's skills in choosing, using media, varying methods and learning resources to achieve HOTS-based learning objectives.